Promote or Inhibit: Economic Goal Pressure and Residents' Health - Zhong, Min; Wang, Peng; Ji, Ming; Zeng, Xi-Hao; Wei, Hong-Xiang (Frontiers in Public Health, 2021)
This paper aimed to identify the relationship between the pressure to reach economic growth targets and residents' health by applying a panel fixed effects model, a Sobel-Goodman mediation effects test and a regulatory effects model to the inland provinces of China. The empirical results verify that the pressure to reach economic growth targets in these regions reduces the level of residents' health. Moreover, the effect in developing regions is significantly stronger than that in developed regions, and the effect in the northern region is significantly stronger than that in the southern region. The mediation effects test found that the pressure to reach economic growth targets has led to an upsurge in PM2.5 concentration and an increase in the output of industrial solid waste, thereby threatening residents' health. The regulatory effects model highlights that enhancing public awareness could weaken the negative impact of the pressure to reach economic growth targets on residents' health, while the expansion of industrial production will aggravate the negative impact. In the process of economic growth, the government should set reasonable economic growth targets, pay attention to the construction of the environmental protection legal system, implement energy- conservation and emission reduction measures and increase public awareness of environmental protection to ensure residents' health.